Liquid-based cervical cytology using ThinPrep technology: weighing the pros and cons in a cost-effectiveness analysis - de Bekker-Grob,E.W.; de Kok,I.M.; Bulten,J.; van Rosmalen,J.; Vedder,J.E.M.; M. Arbyn; Klinkhamer,P.J.J.M.; Siebers,A.G.; van Ballegooijen,M. (Cancer Causes Control, 2012)
PURPOSE:
Keywords: Advantages; alternative; an; Analyses; AS; at; Belgian Foundation Against Cancer; cancer; cancer screening; Cervical; cervical cancer; cervical cancer screening; CERVICAL-CANCER; cervix; Change; cit_Marbyn; conditions; conventional; Cost; Cost effectiveness; Cost-effectiveness; COSTS; cytology; data; ECCG; EU; EUROCHIP; EUROCOURSE; Evaluating; Follow up; FOLLOW-UP; HPV; Human; implementation; IS; Less; Life; method; methods; MODEL; monolayer cytology; Netherlands; ON; PREHDICT; Quality; Quality of Life; RCT; Research; result; results; SCREENING; SENSITIVITY; Strategies; Strategy; System; Test; threshold; triage; values; WOMEN